Analysis of Attitudes and Purchases of Female Consumers towards Green Marketing Related to the Cosmetics Industry in Indonesia - Pratiwi, Mita Adi; Susila, Ihwan (Ekonomi Bisnis, 2024)
The competition between companies extends beyond vying for consumers to include the development of innovations that are beneficial to the environment. Consumers are becoming increasingly discerning in their product choices. This study investigates the impact of female consumers' attitudes on their purchasing behavior towards environmentally friendly cosmetics in Indonesia. Green knowledge, green advertising, and green brand image are critical factors that can enhance company performance. Therefore, this study is essential for identifying the impact of green knowledge, green advertising, and green brand image on purchase intentions through customer attitudes. A quantitative approach with explanatory research was utilized in this study. The purposive sampling technique was employed, involving 126 respondents with prior experience in purchasing environmentally friendly cosmetic products and a preference for such products. Data were analyzed using the Partial Least Squares (PLS) method with SmartPLS 3.0. The findings indicate that green knowledge, green advertising, green brand image, and customer attitudes significantly influence purchase intentions for environmentally friendly cosmetics.